Finite Element Modeling of Soil Settlement Using Rectangular Deep Soil Mixing with Biopolymer Stabilization - Nazhar, Luthfiyanti; Hamdhan, Indra Noer; Amalia, Dewi (ASTONJADRO, 2026)
Unstable subgrade conditions often cause structural and serviceability problems in road infrastructure. To mitigate these problems, soil improvement techniques are needed, one of which is Deep Soil Mixing (DSM). This study presents a numerical investigation of rectangular DSMs with column diameters of 40 cm, 60 cm, and 80 cm. A biopolymer-based stabilization material was used to reduce subsidence and increase stability along the Karanggede–Juwangi Road, Central Java. The mechanical behavior of the soil before and after biopolymer treatment was evaluated. Numerical modeling was performed using the finite element method (FEM) implemented in PLAXIS software to analyze vertical deformation (settlement) and the factor of safety (SF) of slope stability. Biopolymers materials Consisting of chitosan (CHI), guar gum (GG), and xanthan gum (XG)—were used as stabilizing agents in the DSM columns. The results show that the application of DSM combined with biopolymer significantly improves soil performance. All DSM configurations demonstrated reduced soil deformation and increased factor of safety compared to untreated soil conditions. Among the analyzed models, the 80 cm diameter DSM column exhibited the most favorable performance. The incorporation of chitosan (CHI) resulted in a reduction in soil deformation of 70.72%, while guar gum (GG) achieved a 77.55% reduction. The highest deformation reduction was obtained using xanthan gum (XG), reaching 84.88%, indicating its superior stabilization effectiveness. Furthermore, the analysis revealed a substantial improvement in slope stability, as reflected by an increase in the safety factor (SF) ranging from 76.44% to 220.30% compared to the untreated soil condition.